AN EMPIRICAL STUDY OF INTEGRATED REPORTING PRACTICES AS VOLUNTARY DISCLOSURES IN INDIAN ENERGY COMPANIES - Agnihotri, Shivam; Kumar, Pramod; Harit, Kapil; Bharti, Devdutta (Indian Journal of Finance and Banking, 2023)
Integrated Reporting (IR) provides various stakeholders with a wide range of highly informative and analytical value. The literature on IR reflects a positive view towards adopting IR practices, and the Security Exchange Board of India (SEBI) suggested that the top 500 listed entities followed IR practices voluntarily in Feb 2017. Therefore this study examined the trend and disclosure of IR followed by select Indian energy companies in a comparative manner sector-wise and operational area-wise from Financial Year (FY) 2017-18 to 2021-22. The top four electricity and petroleum companies listed on the Bombay Stock Exchange (BSE) based on market capitalization have been selected to examine IR practices. A checklist of 21 contents based on the IR framework is constructed to check the level of IR practices in select energy companies. Late adoption, lack of proper understanding of the IR framework, and common and different reporting trends were found in six select energy companies. These companies should have reported core values such as connectivity of information, conciseness and, reliability & completeness. IR practices of one company fully complied with the IR framework, and the IR practices of another company reflect a need for more connectivity of information only. Petroleum companies disclosed more readable IR practices in one place in the Integrated Annual Report (IAR) compared to electricity companies. Managerial and policy implications suggested at the end of this study should be adopted and enacted by organizations and regulatory authorities, respectively, for the soundness of IR practices from an Indian perspective. JEL Classification Codes: M41, M48, G38.